Nyintak Pedarok, Pengobatan Tradisional Suku Dayak Kerabat di Kabupaten Sekadau - Herlina Herlina Herlina (Jurnal Pendidikan Bahasa, 2023)
This research aims to explain oral literature, especially nyintak pedarok as a traditional medicine for the Dayak Kerabat tribe in Sekadau Regency. In this case, the author analyzes the mantra and meaning of nyintak pedarok. The research method used is descriptive. The form of qualitative research is qualitative. The research approach used is a structural approach. Based on research that has been conducted, nyintak pedarok is a type of traditional medicine that lives among the Dayak Kerabat of Penyapat, in Sekadau Regency, West Kalimantan. This treatment is carried out to treat diseases that cannot be cured medically. This disease is called pedarok. In the treatment of nyintak pedarok there is a simple mantra and it contains the philosophy of life of the Dayak Kerabat community. So, it can be concluded that nyintak pedarok is a simple healing ritual which contains simple mantras and the meaning of beliefs towards the world in it.